PENERAPAN RESTORATIVE JUSTICE SEBAGAI RESOLUSI PEMBERANTASAN TINDAK PIDANA HAK KEKAYAAN INTELEKTUAL DI INDONESIA - Tito Abadia Putra, Muhamad Juliarachim, Sulistyanto Widagdo (GEMA, 2015)
Protection of Intellectual Property Rights is an exclusive rights of the copyright holder. The exclusive rights must be protected from others parties who are not responsible for the use of such rights, such as the use rights without the permission of the owner. In this case, the civil servant investigators from Directorate General of Intellectual Property Rights, as a public servant trying to protect victims in order to avoid excessive losses, to enforce the law in accordance with applicable laws. In addition to dispute resolution through repressive path, for the sake of attention to the interests of both parties, sometimes the dispute is resolved by means of preventive. This reseach tries to give advices in the settlement of disputes in the field of Intellectual Property Rights preventive manner, which is the concept of Restorative Justice in solving the crime of Intellectual Property Rights, its an approach in solving criminal matters involving the victim, the offender, as well as elements community for the creation of a justice. This is expected to consider the interests of the victim is the owner of the rights herein position as the aggrieved party. The study was conducted in the Directorate of Investigation Directorate General of Intellectual Property Rights. This study aims to find a means of solving criminal cases of intellectual property rights more precise and can be perceived as fair by the parties.Â